G2C adoption of e-government in Malaysia: trust, perceived risk and political self-efficacy - Hussein, Ramlah; Mohamad, Norshidah; Ahlan, Abdul Rahman; Mahmud, Murni; Aditiawarman, Umar (IGI Global, 2010)

(untitled)
Electronic government or e-government has long been known as a breakthrough of a new form of communication and transaction between the government and citizens, the government and industries, and among the government agencies. Simply, e-government is meant not only to help the government to accomplish its daily administrative activities but also to provide more easy way to communicate with external entities such as citizens and businesses throughout the utilization of Information and Communication Technology (ICT). With the implementation of e-government in Malaysia, study about Government to Citizens (G2C) adoption could be significantly important in reflecting its progress. Against this backdrop, this research intends to study about G2C adoption in Malaysia by adopting the Technology Acceptance Model (TAM) theory as a framework. Other factors that are believed in influencing citizens’ intention to use G2C system are also examined.